Q. 44.0( 31 Votes )

For the polynomia

Answer :

Put x = -1 throughout the polynomial

m × (-1)2 – 2 × (-1) + 3 = 7


m + 2 + 3 = 7


m + 5 = 7


m = 7-5


m = 2


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Divide polynomialMHB - Math Part-I

For which the valMHB - Math Part-I

<span lang="EN-USMHB - Math Part-I

<span lang="EN-USMHB - Math Part-I

If the polynomialMHB - Math Part-I

If the value of tMHB - Math Part-I

Use factor theoreMHB - Math Part-I

Polynomials <spanMHB - Math Part-I

<span lang="EN-USMHB - Math Part-I

Divide the first MHB - Math Part-I